ANALISIS KINERJA KEUANGAN PERUSAHAAN PADA HOTEL BANNE HARITAGE - Daniel Nemba Dambe; Hima Sukmawati (JURNAL ULET (Utility, Earning and Tax), 2021)
The purpose of this study was to determine the level of financial performance of the Banne Haritage Hotel. The research method used is descriptive method using data from 2016 to 2018. The analytical tools used are liquidity ratios, namely Current ratio and Quick ratio, Solvency, namely Liabilities to capital and Liabilities to assets, and Profitability, namely ROI and ROE. The results showed that the financial performance of Banne Haritage Hotel was good in terms of the current liquidity ratio of 1.93 (2016) and 9.02 (2018), the Quick ratio of 1.68 (2016) and 8.49 (2018). The company's solvency is also classified as both the ratio of liabilities to assets of 0.39 (2016) and 0.28 (2018), Liabilities to capital of 0.04 (2016) and 0.027 (2018). The company's profitability is also classified as good with ROI of 0.18 (2016) and 0.20 (2018).